Step * 1 of Lemma weak-continuity-principle-real-nat


1. : ℝ
2. : ℝ ⟶ ℕ
3. n:ℕ+ ⟶ {y:ℝy ∈ (ℕ+n ⟶ ℤ)} 
4. ∃n:ℕ+((F x) (F (G n)) ∈ ℕ)
⊢ ∃n:{ℕ+((F x) (F (G n)) ∈ ℕ)}
BY
(D -1 THEN UseWitness ⌜n⌝⋅ THEN Auto) }


Latex:


Latex:

1.  x  :  \mBbbR{}
2.  F  :  \mBbbR{}  {}\mrightarrow{}  \mBbbN{}
3.  G  :  n:\mBbbN{}\msupplus{}  {}\mrightarrow{}  \{y:\mBbbR{}|  x  =  y\} 
4.  \mexists{}n:\mBbbN{}\msupplus{}.  ((F  x)  =  (F  (G  n)))
\mvdash{}  \mexists{}n:\{\mBbbN{}\msupplus{}|  ((F  x)  =  (F  (G  n)))\}


By


Latex:
(D  -1  THEN  UseWitness  \mkleeneopen{}n\mkleeneclose{}\mcdot{}  THEN  Auto)




Home Index